Per ascensorius gradus imaginationum: The Mystagogical Teaching of Saint Gertrude (Part 1) - Forastieri, Ana Laura (Cistercian studies quarterly, 2016)
The article focuses on the teaching of Saint Gertrude by Ana Laura Forastieri and mentions teachings of saint Benedict by Pope Francis of the Roman Catholic Church, mystagogy of images by Saint Gertrude and principles from the book, "The Herald of Divine Love". Topics discussed include the book "The Herald of God's Loving-Kindness" and Gertrude's work on pedagogy of images.